A Mobile Application for motor coordination deficiency users - Romero, Roseli Aparecida Francelin; Leite, Tiago Miranda (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
It is not uncommon to find people with manual difficulties due to problems of motor coordination or some physical or neurological deficiency. This can hamper, among other things, the learning of writing digits and letters of the alphabet. In this article, we present a tool, developed in Python, to be used in tablets or phones with Android system. The tool can help users with some kind of hand handicap in the learning of letters or numbers writing, through their interaction with the electronic device. This system uses a CNN for recognizing the letters or digits and to give a feedback positive or negative for the user. Further, it can help users to learn about the corresponding image and sound, for each respective letter or digit. The mobile application is easy to use and has been tested in the learning of autistic children for 4 months. During training, the children demonstrated a good familiarity with the software and improved writing performance.